A corpus-based study of metadiscourse features in Chinese-English simultaneous interpreting - Ren, Wen; Wang, Lu (Frontiers in Psychology, 2023)
Metadiscourse markers have been observed to be frequently employed by simultaneous interpreters as interpreting strategies in the process of interpretation. However, the realm of inquiry into this phenomenon remains relatively underexplored. This study aims to rectify this gap by conducting a systematic analysis of metadiscourse features in the context of Chinese-English simultaneous interpreting. The analytical framework for this study is rooted in Hyland's interpersonal model of metadiscourse. By comparing the frequency and distribution of various metadiscourse markers in the source language (Chinese), target language (English), and original English speeches in simultaneous interpreting events, the research seeks to offer a quantitative description, qualitative analysis, and explanation of the causes of these metadiscourse features. To facilitate this analysis, the authors have compiled a Chinese-English Simultaneous Interpreting Parallel Corpus and a Comparable Original English Corpus based on ten international economic conferences, totaling 161,068 tokens. The findings reveal significant differences in interlingual and intralingual comparisons. Professional interpreters demonstrate a strong awareness of metadiscourse by employing various "metadiscourse interpreting strategies," including explicitation/simplification, emphasis/weakening, and visibility/invisibility. Moreover, interpreted English displays distinct metadiscourse features including explicitation of textual logic, objective modal tendency, and audience orientation, as compared to the original English speeches. The observed differences in the study can be attributed to a range of factors, including contextual factors, source language features, and the cognitive psychology of the interpreter. This study provides an in-depth analysis of metadiscourse characteristics in Chinese-English simultaneous interpreting, contributing to fine-grained inquiries into our understanding of the linguistic features of interpreted texts within the context of corpus-based interpreting studies.